2023
DOI: 10.1182/blood.2022016690
|View full text |Cite
|
Sign up to set email alerts
|

Malignant T cells induce skin barrier defects through cytokine-mediated JAK/STAT signaling in cutaneous T-cell lymphoma

Abstract: Cutaneous T-cell lymphoma (CTCL) is a devastating lymphoid malignancy characterised by accumulation of malignant T cells in the dermis and epidermis. Skin lesions cause serious symptoms hampering the quality of life and are entry sites for bacterial infection - a major cause of morbidity and mortality in advanced disease. What drives the pathological processes that compromise the skin barrier remains unknown. Here, we report on increased transepidermal water loss and compromised expression of skin barrier prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…Aberrant JAK3 activation and its downstream signaling pathways are implicated in the pathogenesis of CTCL, and inhibition of JAK3 has been a therapeutic strategy for CTCL with increasing attentions. Many studies have shown that JAK3 inhibitors had good effects in CTCL cell lines [15,41,42]. For example, Tofacitinib, a JAK3 selective inhibitor, showed inhibitory effects on intracellular growth factor and cytokine-mediated signals.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant JAK3 activation and its downstream signaling pathways are implicated in the pathogenesis of CTCL, and inhibition of JAK3 has been a therapeutic strategy for CTCL with increasing attentions. Many studies have shown that JAK3 inhibitors had good effects in CTCL cell lines [15,41,42]. For example, Tofacitinib, a JAK3 selective inhibitor, showed inhibitory effects on intracellular growth factor and cytokine-mediated signals.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous single-cell RNA sequencing (scRNA-seq) literatures have demonstrated prominent heterogeneity of CTCL cancer cells, both in lesional skin (patch/plaque/tumor) and circulation [30][31][32][33][34][35][36][37] . To decipher the CDK9 expression across different malignant T cell clusters, we analyzed 3 publicly available scRNA-seq datasets containing lesional skin or blood samples from patients with MF mycosis fungoides (MF) or Sézary syndrome (SS) as well as healthy controls 32,34,38 .…”
Section: Cdk9 Is Overexpressed In Ctcl and Defines A Unique Malignant...mentioning
confidence: 99%
“…The JAK/STAT pathway has been found activated in various T-cell lymphomas. 7 Notably, CTCL can exhibit somatic JAK mutations contributing to the dysregulation of JAK/ STAT signaling 8,9 Therefore, this pathway is considered as a novel target for CTCL therapy using specific JAK inhibitors. However, in a phase 2 trial evaluating ruxolitinib in various subtypes of refractory T-cell lymphomas, one only out of 7 MF patients showed a partial response lasting over 18 months.…”
Section: Severe Relapses Of Cutaneous T-cell Lymphoma After Treatment...mentioning
confidence: 99%